1982
DOI: 10.1113/jphysiol.1982.sp014452
|View full text |Cite
|
Sign up to set email alerts
|

Properties of junctional and extrajunctional acetylcholine‐receptor channels in organ cultured human muscle fibres

Abstract: SUMMARY1. Current noise, obtained during steady ionophoretic application of acetylcholine (ACh) to voltage-clamped human fibres has been analysed to derive properties of end-plate channels and also extrajunctional ACh-activated channels which are present at the muscle-tendon junction of normal fibres. In addition, ACh-receptor channels present at the end-plate and tendon region in organ cultured muscles have been compared with those in fresh muscles.2. Extrajunctional channels in the tendon region of fresh fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Thus, in two different species, we find no evidence for topographical segregation of AcCho receptor channel types on innervated muscle. The demonstration that nonsynaptic channels are functionally identical to those at the synapse now explains earlier findings of "junctional-type" channels in nonsynaptic regions of both amphibian (14,(16)(17)(18) and mammalian (6,19) (5). Noise analysis of AcCho-activated currents on human intercostal muscle suggested that synaptic channels had a higher conductance and briefer mean open time than channels at the myotendinous junction.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Thus, in two different species, we find no evidence for topographical segregation of AcCho receptor channel types on innervated muscle. The demonstration that nonsynaptic channels are functionally identical to those at the synapse now explains earlier findings of "junctional-type" channels in nonsynaptic regions of both amphibian (14,(16)(17)(18) and mammalian (6,19) (5). Noise analysis of AcCho-activated currents on human intercostal muscle suggested that synaptic channels had a higher conductance and briefer mean open time than channels at the myotendinous junction.…”
Section: Discussionsupporting
confidence: 59%
“…This finding led to the idea that channels at synaptic regions of innervated muscle are converted to a functionally distinct "mature" form (6,7). The idea of topographical segregation of channel types on innervated muscle was supported by a noise-analysis study that compared synaptic receptor channels to those at the myotendinous ends of the muscle (5). In that study, the receptor channels at the nonsynaptic endings of human intercostal fibers were found to be functionally distinct from those present at the synapse.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This opens the possibility that ACh released from the sensory terminal might activate intrafusal fiberassociated AChRs in the equatorial region. While our studies favor a synapse-like role of AChRs at sensory nerve terminals, it remains possible that the AChRs have an (unknown) non-synaptic role, similar to the AChRs and associated proteins present at the myotendinous junctions (Fertuck and Salpeter, 1976;Cull-Candy et al, 1982;Chen et al, 1990;Bernheim et al, 1996). Clearly further studies are needed to clarify the role of the AChRs in muscle spindle function.…”
Section: Discussionmentioning
confidence: 78%
“…This activation could lead to a contraction of the central part of the intrafusal fiber, potentially reversing the lengthening of the central region due to c-motoneuron activity. Alternatively, AChRs at the central region of muscle spindles might have an unknown function, similar to the myotendinous junctions where AChRs also accumulate, but the functional significance of the AChR aggregates is unknown (Fertuck & Salpeter, 1976;Cull-Candy et al, 1982;Chen et al, 1990;Bernheim et al, 1996).…”
Section: Discussionmentioning
confidence: 99%